Faktor Maternal Dan Pelayanan Ante Natal Care Terintegrasi Pada Kejadian Prematuritas Di Puskesmas Wilayah Kota Palangka Raya - Legawati Legawati; Riyanti Riyanti; Noordiati Noordiati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Premature delivery is a risk factor that causes neonatal death. Various attempts were made to reduce the neonatal mortality rate, such as integrated antenatal care. The purpose of this study is to determine maternal factors and its integrated services that affect the incidence of prematurity at Public Health Center In Region of Palangka Raya. This is a quantitative research. This study proves the bivariate analysis that the integrated Ante Natal Care, factors age maternal, parity, history of labor, employment, social, economic and distance delivery with the incidence of prematurity, while multivariate analysis proves ANC integrated, factors maternal age, occupation, parity and distance delivery to give effect to the incidence of prematurity in the city of Palangkaraya.